THE PROBLEMS OF THE RIGHT TO CLEAN WATER FROM THE SALUKI RIVER FLOW FOR THE POST-DISASTER PASIGALA COMMUNITY - Nursiah Moh Yunus; Rosdian Rosdian; Mohammad Saleh (Cepalo, 2022)
As one of the natural elements needed by humans and other living things, the availability of clean water is essential for the community, especially after the earthquake, tsunami, and liquefaction disasters which hit Palu City Sigi Regency and Donggala Regency (PASIGALA). As time gues on significantly it, it has almost entered its third year after the disaster; this vital issue has developed because the water condition suitable for community consumption, which was previously felt to be abundant and could be used together, is now starting to be limited. Thousands of people only rely on tank cars. Recently, there has been a wise thought that water as common property can be positioned as a vital part of  human right. Therefore, the state should fulfill it as the implementation of control of resources (water) by the state. Article 33, paragraph (3) of the 1945 Constitution of the Republic of Indonesia explicitly governs the state's right to control water resources to achieve people's prosperity. This normative research seeks to explain the fulfillment of the right on water in Indonesia according to conception and philosophy contained in Article 33, paragraph (3) of the 1945 Constitution of the Republic of Indonesia. The focus stands for limiting problems regarding the fulfillment of clean water for the PASIGALA community after the disaster. This study tries to unravel the problems in which: 1) the development of global conceptions and ideas have carried the importance of water resources and their recognition as one of the essential values of human rights.